(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
The murder of Rogelia Cruz Martinez, in January 1968, was part of the Guatemalan counterinsurgency practices. The image of this woman emphasized the no-limits law enforcement operations against the revolutionaries, the impact is imminent in the population, since a decade earlier she had held the title of Miss Guatemala 1959 and participated in the Miss Universe in Long Beach, California. She was part of one of the first revolutionary organizations of Guatemala, the Rebel Armed Forces, at the time of his abduction that took her to be killed cruelly. The image of Rogelia Cruz was part of the Guatemalan revolutionary political ideology, in 1973, the artist Arnold “El Tecolote” Ramirez Amaya painted a portrait of her in the walls of the university campus during the so called muralización. Also, various political organizations have taken her name, however, the story lies in the wording of a martyr, necessary for the mobilization and awareness of the fight, but far from historical reality. Therefore, this is an attempt to delve into the lives of Rogelia Crruz to assist in the historical memory of Guatemala, from the contribution of a woman who made a significant contribution to the revolutionary process of the Central American country.